Assessment and Treatment of Impaired Sensorimotor System in Individuals with Neck Pain - Munlika Sremakaew (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2020)
Neck pain is associated with sensorimotor disturbances including impaired balance. Understanding the differences in neck muscle activity during standing tasks between persons with neck pain and asymptomatic controls may inform rehabilitation approaches. In addition, whether specific sensorimotor control training is required in rehabilitation in neck pain persons with impaired sensorimotor system remains unclear.The first study aimed to investigate and compare neck muscle activity during different standing balance conditions in patients with chronic idiopathic neck pain and asymptomatic controls, and to determine associations between neck muscle activity and postural sway. Participants included 25 with neck pain and 25 controls. Surface electromyography (sEMG) was recorded bilaterally from sternocleidomastoid and splenius capitis muscles. Postural sway was measured using a force-plate. Standing balance was tested under conditions of eyes open and closed; on firm and soft surfaces; in comfortable and narrow stances. The results found that the neck pain group showed higher sEMG activity of sternocleidomastoid and splenius capitis muscles compared to controls in all conditions (all p < 0.05). In the neck pain group, the increase in muscle activity of splenius capitis muscle was more pronounced than that in the sternocleidomastoid muscle during standing, in particular in more challenging conditions. Greater postural sway was displayed in the neck pain group (p < 0.05).There was no correlation between a higher level of the neck muscle activity and a greater postural sway (p > 0.05).The second study aimed to investigate the most effective interventions to improve cervical joint position sense (JPS) and balance in persons with neck pain and to assess the effectiveness of the interventions on neck symptoms and impairments, functional ability, patients’ satisfaction and quality of life. One hundred participants with chronic neck pain with impaired neck proprioception and balance were randomized into four groups, 25 participants for each group: 1) local neck treatment (manual therapy and therapeutic exercise), 2) local neck treatment plus oculomotor/JPS exercises, 3) local neck treatment plus balance exercises, and 4) all treatments. All participants received two treatments per week for 6 weeks. Primary outcomes were postural sway and joint position error (JPE). Secondary outcomes included neck pain intensity and disability, dizziness, cervical range of motion, gait speed, functional ability, patients’ satisfaction, and quality of life. Blinded outcomes measures were taken at baseline, after treatment, and at a 3-month follow-up. The results demonstrated that there was no loss to followup. All groups improved in primary and secondary outcome measures both after treatment and 3-month follow-up (p < 0.05). Overall results when compared to group 1, participants in groups 3 and 4 had greater reduced postural sway (sway area and displacement in the anterior-posterior direction) (p < 0.05) and participants in groups 2 and 4 had greater decreased cervical JPE (rotation) (p < 0.05). No differences between groups were found in secondary outcomes (all p > 0.05).This thesis suggests that increased neck muscle activity may compensate for postural instability in persons with chronic idiopathic neck pain reinforcing the need for balance training to lessen unwanted neck muscle activity. Additionally, sensorimotor disturbances associated with neck pain are more effectively addressed with specific sensorimotor control training. The overall findings highlight an important contribution of the sensorimotor function to neck pain, which should be considered in rehabilitation of persons suffering from chronic idiopathic neck pain.